A LEGAL REVIEW OF CUSTOMARY MARRIAGE IN THE VILLAGE OF GUMANTAR, WITH PARTICULAR REFERENCE TO THE LAW OF MARRIAGE - Wahyudin, Wahyudin; Syahrial Haq, Hilman; Amalia, Fitriani (Media Keadilan: Jurnal Ilmu Hukum, 2024)
This research aims to ascertain the historical and procedural aspects of merarik custom in Gumantar Village, Kayangan District, North Lombok Regency. In order to achieve this, the research will examine the following: "Juridical Review of Customary Marriage in Gumantar Village Viewed from the Marriage Law". Furthermore, the research will investigate the application and legal arrangements pertaining to underage marriage in Gumantar Village. Consequently, the following problems and issues have been identified: (1) What is the nature of Merarik Custom in Gumantar Village, Kayangan District, North Lombok Regency? (2) What are the legal arrangements for underage customary marriage in Gumantar Village, based on Law No. 16 of 2019? The research methodology employed in this study is a combination of normative and empirical research. The approaches utilized include empirical, legal, sociological, and historical methodologies. The findings of this study indicate that customary marriage in Gumantar Village is still largely governed by customary processes. The concept of marriage as defined by custom is of interest not only to the individuals involved in the marriage, but also to the wider community in Gumantar Village. However, there are instances where customary marriages in Gumantar Village deviate from existing regulations due to the prevalence of underage marriages. Nevertheless, this custom should not be abandoned and must still be carried out in a way that traditional leaders and the community are expected to be able to adapt customary law to national law, so that customary law and state law are in harmony